Fuel injection parameters study for low exhaust emissions of a common-rail diesel engine fueled with different biodisesels' blend / How Heoy Geok - How , Heoy Geok (2018)
Nowadays, the use of diesel engines is increasing rapidly due to their superior fuel economy, higher efficiency and excellent reliability. The energy crisis of fossil fuel depletion, rising price of diesel and environmental degradation have triggered a search for clean, sustainable and alternative fuels for internal combustion engines. Biodiesel is one of the most promising alternative fuels because it is a biodegradable, non-toxic and renewable fuel. This research aims to produce biodiesel from different feedstock such as coconut, calophyllum inophyllum and moringa oleifera oil and tested in a medium-duty four-cylinder diesel engine. In addition, the in-house produced coconut biodiesel was also used in the study of the effects of biodiesel blends, fuel injection timing, split injection schemes, injection dwell angle and mass ratio on the engine performance, emissions and combustion characteristics. At the first stage, a detailed investigation and characterization of key physicochemical properties were carried out. This was followed by the investigation of the effects of the usage of all these biodiesel blends on engine performance, emissions, exhaust particulate matter and combustion under different engine operating conditions. At second stage, parametric studies relating with start of injection timing variation and multiple injection schemes using COB20 and COB50 blends were performed and benchmarked with petroleum diesel fuel as baseline. At the final stage, the impact of two-stage injection dwell angle and mass ratio on engine performance, emissions and combustion characteristics using coconut biodiesel blends were investigated. The results showed that all biodiesel fuels and its blends have physicochemical properties relatively close to those of petroleum diesel. The experimental results also suggested that there are some penalties in engine brake power, brake specific fuel consumption (BSFC), and nitrogen oxide (NOx) blends with the presence of biodiesel fuel in the blend. The second stage experimental results revealed that a remarkably lower NOx level below 100 ppm can be obtained by retard SOI timing for both of the COB20 and COB50 fuel operations and with triple injection scheme. Multiple split injections is a practical strategies to simultaneously decrease NOx and smoke emissions when the SOI timing is fine-tuned and is an ideal alternative to operate with biodiesel fuel. For the last stage experiment, the results showed that exhaust emissions, engine performance and combustion characteristics are substantially affected by types of fuel and SOI timing but slightly influenced by two-stage injection dwell angle. Also, a considerably lower level of NOx below 90 ppm is achievable via late SOI timing for fuel operations conducted using COB20 or COB50 biodiesel blends with injection mass ratio of 25:75. Overall, the results indicated that biodiesel from coconut, calophyllum inophyllum and moringa oleifera oil can be used satisfactorily in the modern high-pressure common-rail diesel engine without modification. Besides, the results revealed that multiple and two-stage fuel injection with different mass ratio and dwell angle are practical strategies to simultaneously decrease NOx and smoke emissions when the SOI timing is fine-tuned and is an ideal alternative to operate with biodiesel fuel.